DAMPAK KETERBUKAAN EKONOMI TERHADAP PENYERAPAN TENAGA KERJA DI INDONESIA TAHUN 1993-2022 - Sahrul Sahrul; Stelamis Metekhoy; Djufri Rays Pattilouw; Maryam Sangadji (LPPM Institut Pendidikan Nusantara Global, 2023)
Indonesia's population growth every year is increasing. Population growth certainly results in an increase in the number of labor force. However, this will become a problem in the world of work if the increasing number of labor force is not proportional to the amount of labor absorption. This problem is very important considering its relation to the level of social welfare. This study aims to determine the impact of economic openness on employment in Indonesia. This research is a quantitative study and uses time series data, namely Export, Exchange Rate, FDI and Labor data using the ECM model. The results of this study indicate that in the long run Exports, Exchange Rates and FDI have a positive and significant effect on Absorption of Labor in Indonesia. Whereas in the short term Exports, Exchange Rates and FDI have a positive and insignificant effect on the Absorption of Labor in Indonesia in 1993-2022. And the ECT value in the short term has a negative and insignificant effect which indicates that there is a short-term imbalance in the long term.